Іnstitutionalization of innovation transformations of agricultural production in the context of providing economic security - Pavlova, Halina; Павлова, Галина Євгеніївна; Honcharenko, Oksana; Гончаренко, Оксана Володимирівна; Yakubenko, Yuliya; Якубенко, Юлія Леонідівна (Національний університет "Чернігівська політехніка", 2018)
Urgency oftheresearch. Competitive development and ensuring of economic security of the country determine the need for intensification of the innovation process in agricultural and industrial production. The achievement of these imperatives is due to their institutionalization, which determines the relevance of the research topic.Target setting. Due to the lack of a systemic base for the development of agricultural and industrial production, the pri-orities of the industry are uncoordinated, there are no results of innovative changes. It is the institutionalization of innovation transformations, ensuring of the systematic interaction of insti-tutes can certify the achievement of strategic priorities for the development of agricultural and industrial production.Actual scientific researches and issues analysis. In-strumentation of institutionalism for the formation of the con-ceptual regulations of innovative development and determina-tion of its determinants were used by A. Balyan, O.Datsiy, L.Kurilo, I. Kostyrko, P. Sabluk, M. Malik, S. Tivonchuk, L.Fedulova, O. Shpykulyak, O. Shubravska.Uninvestigatedparts of general mattersdefining. The need to define conceptual regulations for the formation of innovation development leads to further study of the problems related to the methodology of institutional transformations and the peculiarities of the institutional security.The research objective. The purpose of the article is to determine the peculiarities of institutionalization of innovative transformations of a g r i c u l t u r a l a n d i n d u s t r i aproduction, its characteristic features and constituent elements.The statement of basic materials. The article substantiates the importance of developing innovations in the agrarian sector to ensure the country's food security. The purposefulness of innovation development on the basis of implementing innovative policy tools leads to the introduction of regulatory, signalling and stimulating institutions.Conclusions.To ensure the activation of the innovation process, it is necessary to develop an appropriate institutional mechanism that is capable of implementing the priorities of innovation development at the level of the industry and re-gionsand the growth of producers’ innovation activity. Актуальність теми дослідження.Конкурентоспо-роможнийрозвиток та забезпечення економічної безпеки країни обумовлюють потребу в активізації інноваційного процесу в агропромисловому виробництві. Досягнення зазначених імперативів пов’язане з їх інституціоналіза-цію, що зумовлює актуальність теми дослідження.Постановка проблеми.Через відсутність систем-ної основи розвитку агропромислового виробництва неузгодженими постають пріоритети розвитку галузі, відсутні результати інноваційних перетворень. Саме інституціоналізація інноваційних перетворень, забезпе-чення системної взаємодії інститутів може забезпечити досягнення стратегічних пріоритетів розвитку агроп-ромислового виробництва.Аналіз останніх досліджень і публікацій. Інстру-ментарій інституці-оналізму для формування концепту-альних положень інноваційного розвиткута визначення його детермінант використовували А. Балян, О.Дацій, Л.Курило, І. Костирко, П. Саблук, М. Малік, С. Тивончук, Л. Федулова, О. Шпикуляк О. Шубравська.Виділення недосліджених частин загальної про-блеми.Необхідність визначення концептуальних поло-жень формування інноваційного розвитку зумовлює по-дальше вивчення проблем, що стосуються методології інституці-ональних трансформацій та їх інституціона-льного забезпечення.Постановка завдання.Метою статті є визначення особливостей інституціоналізаціїінноваційних транс-формацій агропромислового виробництва, її характер-них ознак і складових елементів.Виклад основного матеріалу.В статті обґрунтовується важливість розвитку інновацій в аграрній сфери для забезпечення продовольчої безпеки країни. Цілеспрямованість інноваційного розвитку на основі реалізації інструментів інноваційної політики зумовлює запровадження регулюючих, сигнальних і стимулюючих інституції.Висновки.Для забезпечення активізації інноваційного процесу необхідна розробка відповідного інституціонального механізму, який здатний реалізувати пріоритети інноваційногорозвитку на рівні галузі і регіонів та зростання інноваційної активності виробників.
Інституціоналізація інноваційних трансформацій агропромислового виробництва в контексті забезпечення економічної безпеки
Keywords: agro-industrial production; агропромислове виробництво; innovation; інновація; innovation development; інноваційний розвиток; innovation priorities; інноваційні пріоритети; institutionalization; інституціоналізація